REVIEW ARTIKEL: AKTIVITAS DAUN MURBEI (MORUS ALBA L.) SEBAGAI ANTIMALARIA - Lika Ginanti Febriana; Anas Subarnas (Farmaka, 2022)
Malaria adalah penyakit yang disebabkan oleh infeksi Plasmodium yang terinfeksi nyamuk betina Anopheles. Malaria masih menjadi penyebab utama kematian di seluruh dunia. Masalah utama dalam program pengendalian malaria global adalah meningkatnya kejadian resistensi terhadap obat antimalarial. Pengembangan herbal daun Morus alba Linn. menjadi salah solusi dalam mendukung penanganan malaria. Oleh karena itu, diperlukan pengkajian kandungan  bioaktif daun Morus alba Linn. yang memiliki aktivitas antimalaria. Daun Morus alba L.) memiliki aktivitas antimalaria dengan adanya kandungan senyawa bioaktif flavonoid, polifenol, dan senyawa lainnya dengan mekanisme potensial sebagai antioksidan, imunomodulator, penghambatan sintesis protein, dan gangguan invasi parasit dari eritrosit baru yang telah  teruji secara in vitro dan in vivo dapat melawan infeksi Plasmmodium, sehingga daun Morus alba Linn dapat dijadikan salah satu herbal potensial dalam penanganan malaria.ABSTRACTMalaria is a disease caused by Plasmodium infection which is infected by the female Anopheles mosquito. Malaria is found in Africa and some countries in Asia. The main problem in the global malaria control program is the increasing incidence of resistance to antimalarial drugs. Morus alba L leaf herbal development. become one of the solutions in supporting the handling of malaria. The research method used was a literature review, literature search using keywords Morus alba L.", "Antimalarial Activity of Morus alba Leaf", and "Antimalaria" with a publication year of 10 years. The literature that includes the inclusion criteria is 11 scientific articles. Therefore, it is necessary to study the bioactive content of Morus alba L leaves. which has antimalarial activity. Morus alba L.) leaves have antimalarial activity in the presence of flavonoid bioactive compounds, polyphenols, and other compounds with potential mechanisms as antioxidants, immunomodulators, inhibition of protein synthesis, and interference with the parasitic invasion of new erythrocytes that have been tested in vitro and in vivo. against Plasmodium infection, so Morus alba L leaves can be used as a potential herb in the treatment of malaria.